On Extraction and Extraposition in German. - Lutz, Uli (John Benjamins Pub. Co., 1996)
Extraction has traditionally been one of the main topics in generative grammar, and it retains this status in current variants of the theory. German provides a good testing ground for traditional as well as current theories of extraction. The nine contributions to this volume document the recent lively discussions on the adequate analyses of extraction constructions, on the impact of extraction on semantic interpretation, and, above all, on the question of which constructions are to be analysed as extractions and which not. Uli Lutz gives an overview of extraction theory. Marga Reis challenges.